A large series of extracorporeal shockwave lithotripsy in the very elderly. (August 2019) - Lamacchia, Guilherme Braga; Korkes, Fernando; Baccaglini, Willy; de Mello, Luiz Gustavo Miolaro; Szwarc, Marcelo; Tobias-Machado, Marcos
Background: The incidence of urinary lithiasis has been increasing in recent decades at all ages, including the elderly. In parallel, the world population is aging and there is a paucity of data on treatment of urinary stones in very elderly people. Our main objective was to evaluate the effects of extracorporeal shockwave lithotripsy (ESWL) in patients older than 75 years, and the characteristics of this population. Complications and mortality rates after this procedure in octogenarians were also described. Methods: We retrospectively evaluated very elderly patients who underwent ESWL at our institution from 1998 to 2015, through chart review, telephone interviews, and consultation with the municipal mortality information program. Measured outcomes included demographic and clinical data, ESWL characteristics and complications, interval between ESWL and death, and cause of death. Results: Demographic and treatment characteristics were similar between very elderly and younger patients who underwent ESWL during the same period. No severe complications occurred among older patients. Octogenarians treated in our cohort had a significant life expectancy when ESWL procedures were performed. Even though 38.9% of the patients passed away during the studied period, mortality occurred on average 4.38 years after the ESWL session. Conclusions: In conclusion, ESWL has been used by urologists as a first-line treatment for uncomplicated urinary calculi in very elderly patients. Despite changes associated with aging, and the high prevalence of comorbidities, this procedure seems to be safe and well tolerated in elderly people.